Addressing the "Union Problem" during the Great Recession: State Approaches to Reforming Collective Bargaining. (September 2019) - Wade, Magic M.
Conventional narratives suggest that during the Great Recession, Republican-controlled state governments seized a political opportunity to de-unionize labor strongholds by enacting sweeping right-to-work laws. However, I contend that two distinct reform approaches were pursued during the recession. One type aimed to restrict the ability of unions to organize and maintain membership (the "right-to-work" approach), while the other sought to constrain collective bargaining without hampering union organizing. My analysis of 2, 545 labor relations bills introduced across the U.S. States from 2007 to 2014 confirms the existence of two broad models of reform, each with differing implications for organized labor and partisan politics.